Normal human microbiota and dysbiosis - implications for health and disease - Božić, Dragana; Milenković, Marina; Antić Stanković, Jelena; Arsenović-Ranin, Nevena; Bufan, Biljana (Archives of Pharmacy, 2024)
The normal human microbiota, formerly called the "microbial flora," consists of bacteria, fungi, viruses, and parasites that colonise the skin and mucous membranes of the respiratory, gastrointestinal, and genitourinary tracts. The number and diversity of microorganisms varies between different body niches and is greatest in the intestinal tract. The microbiota contributes to the homeostasis of the human organism by preventing colonisation by pathogenic microorganisms, participating in digestive processes and metabolism, and regulating immune functions. Various environmental and genetic factors can lead to an imbalance in the human microbiota, called dysbiosis, which can affect human health. Dysbiosis is usually the result of decreased microbial diversity and a lower number of saprophytic microorganisms, followed by an overgrowth of opportunistic species. The most common diseases directly related to intestinal dysbiosis are antibiotic-associated diarrhoea and pseudomembranous colitis, both of which are associated with the excessive growth of harmful bacteria and Clostridioides difficile following broad-spectrum antibiotic therapy. Dysbiosis is associated with various health conditions or diseases such as acne, psoriasis, eczema, chronic obstructive pulmonary disease, inflammatory bowel disease, obesity, metabolic syndrome, type 2 diabetes, autoimmune diseases and allergies, neurological diseases such as Parkinson's disease, Alzheimer's disease, epilepsy and stroke, depression, anxiety, infertility, preterm birth, and malignancies.
Keywords: human microbiota; dysbiosis; commensal bacteria; dysbiosis-associated diseases